PENGEMBANGAN PERANGKAT PEMBELAJARAN PERSEGI PANJANG DAN PERSEGI BERBASIS KARAKTER KREATIF MENGGUNAKAN MODEL MISSOURI MATHEMATICS PROJECT (MMP) PADA KELAS VII SMP - Rouf, Abdur; Trapsilasiwi, Dinawati; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2016)
Abstract. This research aims to develop and produce creative character-based learning device in the rectangular and square sub chapters at seventh grade of junior high School (SMP) which have valid, practical and effective criteria. Learning device developed among them is the implementation plan of learning and student worksheets. Development of this learning device using the model of Missouri Mathematics Project (MMP) which consists of 5 stages including riview, development, cooperative work, independent work and projects. Learning device were developed based on the modified 4-D development model by Thiagarajan, Semmel, and Semmel. The development of this learning device consists of defining, designing and developing phases. The subject of this research is the students of class VII A SMPN 1 Silo. The instruments of data collection from this research are: validity sheet, student worksheet, teacher activity observation sheet, student activity observation sheet, teacher questionnaire, and reader sheet of student worksheet. Based on data analysis, this study has three results. First, the learning divice developed have valid criteria. Secondly, the learning device developed have practical criteria based on teacher activity observation sheets and teacher response sheets. Third, the learning device developed have effective criteria based on the effectiveness value in student worksheets, student activity observation sheets, and student activeness score sheet Keywords: Creative character, learning device, model Missouri Mathematics Project(MMP), devepment on the modified 4-D